SUPPORT SYSTEMS AND LEARNER RESILIENCE IN DISTANCE ENGLISH HIGHER EDUCATION - Sri Ardiasih, Lidwina; Juhana; Syafri, Frimadhona; Rahmiaty; Meylina; Sik Chung, Kwang (University of Kuningan, 2025)
This study examined distance learner resilience in overcoming academic burnout during their research in the English department. The descriptive qualitative and quantitative approaches were used to evaluate the experiences and perspectives of 144 distance learners on their self-directed learning activities from the Undergraduate and Graduate English Education Study Programs at Universitas Terbuka (UT). The findings revealed that a strong support system is important in enhancing learners' resilience in distance higher education. Support from family and institutions contributes to their emotional and academic stability, while community engagement and access to digital resources expand learning opportunities and overcome barriers. In addition, the balance between online learning and personal life is key to preventing academic burnout and maintaining learning motivation. Therefore, educational institutions need to develop holistic support strategies, covering emotional, social, and managerial aspects for distance learners.